ON THE CONVERGENCE DOMAIN OF COMPLEX SERIES (Лучшие интеллектуальные исследования, 2025)
Annotation. This article studies power series with complex variables and their convergence domain. Some properties of converging series are presented. The radius of convergence of a power series is studied.Аннотация. В статье изучаются степенные ряды с комплексными переменными и область их сходимости. Приведены некоторые свойства сходящихся рядов. Изучен радиус подхода горизонтального ряда.